Estimations de la production et de la distribution de la biomasse dans la zone de projet PEI en 1985 d'apres les valeurs NDVI obtenues par satellite - Wagenaar, K.T.; Ridder, N.A. de (CIPEA, 1986)
Presents the results of the National Oceanographic and Atmospheric Administration (NOAA) satellite calibration exercise obtained during the 1985 rainfall season field work as undertaken in the context of the Niger/USAID Tufts university/ILCA contract. Includes theoretical background of radio-reflectance, data collections and analysis at three levels, i.e., ground, aerial survey, and satellite.